Penilaian Kerentanan Bangunan Terhadap Gempa Bumi pada Gedung Perkuliahan Berlantai Tinggi di Yogyakarta - Muhammad Heri Zulfiar; Muhammad Irhab Indrastata Zai (Civil Engineering Department, Universitas Muhammadiyah Yogyakarta, 2021)
Yogyakarta, an area that has a high level of risk for earthquakes, can result into potential damage to the buildings erected it. The earthquake that occurred on May 27 th 2006 still leaving a trauma, according to BNPB (2012) the yogyakarta quake caused 4.674 people die and 19.897 others had seriously injuries. Most victims were caused by the falling building and materials. This disaster caused heavy damage to buildings at 96.790, with 117.075 moderate damage, and as well as 156.971. The construction of the new building in Yogyakarta is expected to be able to apply the principles of the earthquake resistant building to minimize the impact of it. Dasron Hamid Research and Innovation Center is the one of building which currently under construction that apply the principles. This research aim to determine the level of vulnerability of RIC buildings to earthquakes using RVS (Rapid Visual Screening) based on FEMA P-154 2015. It was carried out by quantitative methods and direct observation at the construction site by filling in the FEMA P-154 form, this building is consist of 8 floor with 1 ground floor. The form that used is a high seismic type, which means the level of seismicity in the research location has a high earthquake spread. Based on the research, was got result obtain value of 2,3 with the vulnerability of the building to collapse is 0,5%, so the building is safe against earthquakes. This is because the building is erected after a reference or code exists even though it has irregularities such as vertical irregularity and, plan irregularity.Â